Spatial analyses of the 2011 Joplin tornado mortality: deaths by interpolated damage zones and location of victims - Paul, Bimal K.; Stimers, Mitchel James (My University, 2014)
On 22 May 2011, a massive tornado tore through a densely populated section of Joplin, Missouri, killing 162 people. The EF5 tornado was the deadliest single tornado to occur in the United States since modern record keeping began in 1950, surpassing the tornado of 8 June 1953, which claimed 116 lives in Flint, Michigan. The Joplin tornado death toll was also far higher than the average annual number of deaths caused by tornadoes in the United States between 2000 and 2011. This study analyzed Joplin deaths by damage zone and place of death. Tabular data collected primarily from secondary sources revealed the number of deaths and death rates differ significantly by zone of destruction. The central zone (labeled as “catastrophic”) had the most deaths, with the number decreasing systematically in both directions from the center of that zone. The results of this study further show that more people died in nonresidential buildings in Joplin than is usual in a U.S. tornado event, calling into question how well such structures protect occupants. Finally, the lack of basements in residential and other structures most likely contributed greatly to the high death toll, although the degree remains uncertain. Several recommendations are offered to reduce future U.S. tornado fatalities.
Keywords: Joplin, Missouri; Tornado mortality